Campus Sexual Violence: A Comparison of International and Domestic Students - Fethi, Ihssane; Daigneault, Isabelle; Bergeron, Manon; Hébert, Martine; Lavoie, Francine (Journal of International Students, 2022)
The current study used an intersectional framework to investigate international students' experiences of sexual violence and examine differences in contexts, consequences, and disclosure between international and domestic students. Secondary analyses (chi-squares, multivariate logistic regressions) were conducted on previously collected data. The sample consisted of 6,554 students, including 764 international students. Compared with their domestic peers, international students of all ages, genders, sexual orientations, minority status, grade levels, and time spent at university faced an increased likelihood of being the target of sexual violence. Contexts and disclosure of victimization did not vary by student status. International students reported more PTSD symptoms after campus sexual violence. Future studies are needed to determine why perpetrators target international students. Prevention and intervention efforts need to acknowledge diversity among international students and potential victims who could be men, women, LGBTQ+ students, undergraduate and graduate students.